1995
DOI: 10.1083/jcb.129.6.1473
|View full text |Cite
|
Sign up to set email alerts
|

The overgrown hematopoietic organs-31 tumor suppressor gene of Drosophila encodes an Importin-like protein accumulating in the nucleus at the onset of mitosis.

Abstract: Abstract. The tumor suppressor gene overgrown hematopoietic organs-31 (oho31) of Drosophila encodes a protein with extensive homology to the Importin protein of Xenopus (50% identity), the related yeast SRP1 protein, and the mammalian hSRP1 and RCH1 proteins. A strong reduction in the expression of oho31 by a P element inserted in the 5' untranslated region of the oho31 transcript or a complete inactivation of oho31 by imprecise P element excision leads to malignant development of the hematopoietic organs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 48 publications
2
62
0
1
Order By: Relevance
“…These two receptors, variously referred to as importin-␣/pendulin/Rch1/ hSrp1␣/␣-P1/PTAC58/karyopherin ␣2 (9,16,21,25,49,56) and Srp1/karyopherin-␣/NPI-1/␣-S1 (8,34,36,58), bind directly to NLSs and, along with a second, armadillo repeatcontaining subunit (importin-␤/p97/karyopherin-␤) (8), dock the NLS-bearing substrate at the nuclear pore (7,14,21,40,56). Subsequent transport steps are GTP/GDP dependent and involve movement of the NLS receptor and NLS-bearing substrate together as a complex through the pore into the nucleoplasm (2,15,32,35).…”
mentioning
confidence: 99%
“…These two receptors, variously referred to as importin-␣/pendulin/Rch1/ hSrp1␣/␣-P1/PTAC58/karyopherin ␣2 (9,16,21,25,49,56) and Srp1/karyopherin-␣/NPI-1/␣-S1 (8,34,36,58), bind directly to NLSs and, along with a second, armadillo repeatcontaining subunit (importin-␤/p97/karyopherin-␤) (8), dock the NLS-bearing substrate at the nuclear pore (7,14,21,40,56). Subsequent transport steps are GTP/GDP dependent and involve movement of the NLS receptor and NLS-bearing substrate together as a complex through the pore into the nucleoplasm (2,15,32,35).…”
mentioning
confidence: 99%
“…cut15-85 mutants do not have gross defects in nuclear protein import, suggesting that the cut phenotype is not due to failure in protein import. The Drosophila melanogaster importin ␣2 pendulin may also have a direct role in mitosis because it accumulates in embryonic nuclei at the onset of mitosis (Kussel and Frasch, 1995a;Torok et al, 1995). Although these results have been suggestive of a nontransport role in mitosis for members of the importin ␣ family, only the sequestration and release of TPX2 from importin ␣ to regulate mitotic spindle assembly has been directly implicated in a mitotic function (Gruss et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
“…Drosophila melanogaster pendulin (an ␣2) and S. pombe Cut15p (an ␣1) exhibit a similar mitotic nuclear localization. Pendulin accumulates rapidly in the nucleus at the onset of prophase of early embryos (Kussel and Frasch, 1995a;Torok et al, 1995). The intensity of nuclear staining decreases through metaphase and anaphase and increases again at telophase.…”
mentioning
confidence: 99%
“…PTAC 58 showed a 93% amino acid identity with human Rchl, 61% with Xenopus importin a (GORLICH et al, 1994), 52% with Drosophila pendulin (overgrown hematopoietic organs-31; oho 31) (TOROK et al, 1995;KUSSEL and FRASCH, 1995), and 46% with yeast Srplp (YANO et al, 1992). These proteins contain central tandem repeats known as the arm motif, which was first identified in the Drosophila segment polarity gene armadillo (RIGGLEMAN et al, 1989).…”
Section: Ptac 58mentioning
confidence: 99%
“…Recently, it was found that Srpl exists in yeast cytosol in a complex with an essential homologue of karyopherin 3 (PTAC 97) (ENENKEL et al, 1995). Drosophila pendulin was identified as the tumor suppresser gene and its subcellular localization in proliferating tissues was of interest (TOROK et al, 1995;KUSSEL and FRASCH, 1995). That is, during the interphase, the protein is present in the cytoplasm but accumulates in the nucleus at the onset of mitosis.…”
Section: Ptac 58mentioning
confidence: 99%